Digital Trade, Data Protection and EU Adequacy Decisions - Martina Ferracane; Bernard Hoekman; Erik van der Marel; Filippo Santi (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2023)
Using a structural gravity model, we assess whether EU adequacy decisions on data protection are associated with bilateral digital trade. Controlling for digital-relevant bilateral covariates, including preferential trade agreements with digital trade provisions and other data flow arrangements, we find that countries that obtained EU adequacy exhibit an increase in digital trade ranging between 6-14 percent, representing a trade cost reduction up to 9 percent. This is mostly driven by EU adequacy arrangements with the U.S., reflecting the dominance of the EU and U.S. in global digital trade. Countries granted EU adequacy exhibit more digital trade between each other, suggestive of a club effect. Complementary country-specific analysis of post-adequacy digital trade performance using synthetic control methods confirms our findings.
Keywords: D18; F13; F14: K24; L88; O38; 330; Digital trade; data protection; mutual recognition; regulatory equivalence; clubs